Effect of Electrical Stimulation on Blood Flow in Calf Muscles in Different Body Positions - Julius Dovydaitis; Albinas Grūnovas (Lithuanian Sports University, 2018)
Background.  In  most  studies  on  cardiovascular  system,  testing  of  subjects  was  performed  in  a  horizontal position. With the change of the body position, certain functional changes occur in the cardiovascular system. The aim of this study was to analyze the effect of electrical muscle stimulation (EMS) on arterial and venous blood flows. Methods. Eighteen athletes aged 19-23 performed two sessions of tests in horizontal and sitting positions. Changes in arterial and venous blood flows were recorded before and after EMS. In each session two occlusions were performed. In the horizontal position, the initial occlusion pressure of 20 mmHg was applied and as the balance in arterial and venous blood flow rates was reached, the additional pressure of 20 mmHg (40  mmHg in total). In the sitting position, the occlusion pressure of 40 and 20 mmHg was applied respectively (60 mmHg in total). In both sessions EMS was performed using the electrical stimulator Mioritm 021. Results. In both horizontal and vertical positions, the effect of EMS on arterial blood flow, venous reserve capacity and venous elasticity was insignificant. Arterial and venous blood flows was affected significantly by the change of the body position. In the sitting position, arterial blood flow was significantly (p < .05) lower compared to the horizontal position. Similar results were recorded in venous reserve capacity. Conclusion.  The  study  suggests  that  blood  flow  in  the  calf  muscles  is  affected  by  the  body  position  and hydrostatic pressure; arterial blood flow increases in the horizontal body position. Keywords:  electrical muscle stimulation (EMS), arterial blood flow, venous reserve capacity, venous elasticity